THE INFLUENCE OF CLIMATE WARMING ON THE PRODUCTIVITY OF EGGPLANT AND SWEET PEPPER IN THE STEPPE ZONE OF UKRAINE - Polevoy, A. M.; Bozhko, L. E.; Barsukova, E. A.; Kostiukievych, T. K. (Scientific Progress & Innovations, 2022)
Article presents the results of the research of the impact of the environment on the productivity of heat- and moisture-loving vegetable crops of eggplant and sweet pepper. Research used observational data on the development of eggplant and sweet pepper, averaged over regions in the Steppe zone of Ukraine, as well as meteorological elements for the period from 1995 to 2018 and calculated according to the climate change scenario RCP 8.5 for the period up to 2050. It is determined that by 2018, air temperature in the steppe zone of Ukraine increased by 1.2–1.3 °C depending on the territory. This global warming facilitated the increase in sum of temperatures during the growing season of eggplant and sweet peppers, as well as increase in the heat supply during growing season, which allowed to expand the production area of late-maturing and more high-yielding varieties of eggplant and sweet peppers. Besides that, increase of heat supply will extend the northern border of production of heat-loving crops to the central regions of the Forest-Steppe zone of Ukraine. The amount of precipitation during the summer period decreased to 80 % of the long-term average. The average long-term irrigation rate was 3600 m3/ha. Thus, as the amount of precipitation decreased, the inflow of moisture into the soil decreased as well. The increase of air temperature and the decrease of the amount of precipitation combined with the average rate of irrigation led to an increase in evaporation and total evaporation, which, in turn, led to an increase in the evaporation deficit and deterioration of wet conditions for plants. In such conditions heat and moisture supply, as well as crop productivity, decreases, especially during the second half of the growing season. Estimates for the period up to 2050 under the climate change scenario indicate that global warming will continue. The sum of temperatures will increase by 150–180 °C, the amount of precipitation will decrease. This in turn will increase total evaporation, plant moisture consumption and evaporation deficit. Thus, with a constant rate of irrigation, the moisture content of plants will decrease. Increase of irrigation rates will help to increase crop productivity. Calculations of crop productivity at irrigation rates up to 4000 m3/ha showed that the productivity of eggplant and sweet pepper will increase. Therefore, irrigation rates must be adjusted according to crop requirements for wet conditions.